*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **a = a ( t ) = t and g ( t ) = t 2 , becomes v 1 ( t ) e t + v 2 ( t )( t + 1) = 0 , v 1 ( t ) e t + v 2 ( t ) = t 2 t = t. Subtracting the second equation from the Frst one, we get tv 2 ( t ) = t v 2 ( t ) = 1 v 2 ( t ) = t. Substituting v 2 ( t ) into the Frst equation yields v 1 ( t ) e t ( t + 1) = 0 v 1 ( t ) = ( t + 1) e t v 1 ( t ) = Z ( t + 1) e t dt = ( t + 1) e t + Z e t dt = ( t + 2) e t . 224...

View
Full
Document